Measurement of glomerular filtration rate by dynamic contrast‐enhanced magnetic resonance imaging using a subject‐specific two‐compartment model. Issue 7 (13th April 2016) - Tipirneni‐Sajja, Aaryani; Loeffler, Ralf B.; Oesingmann, Niels; Bissler, John; Song, Ruitian; McCarville, Beth; Jones, Deborah P.; Hudson, Melissa; Spunt, Sheri L.; Hillenbrand, Claudia M.
Abstract: Measuring glomerular filtration rate (GFR) by dynamic contrast‐enhanced (DCE) magnetic resonance imaging (MRI) as part of standard of care clinical MRI exams (e.g., in pediatric solid tumor patients) has the potential to reduce diagnostic burden. However, enthusiasm for this relatively new GFR test may be curbed by the limited amount of cross‐calibration studies with reference GFR techniques and the vast variety of MR tracer model algorithms causing confusion on the choice of model. To advance MRI‐based GFR quantification via improved GFR modeling and comparison with associated 99m Tc‐DTPA‐GFR, 29 long‐term Wilms' tumor survivors (19.0–43.3 years, [median 32.0 ± 6.0 years]) treated with nephrectomy, nonnephrotoxic chemotherapy ± radiotherapy underwent MRI with Gd‐DTPA administration and a 99m Tc‐DTPA GFR test. For DCE‐MRI‐based GFR estimation, a subject‐specific two‐compartment (SS‐2C) model was developed that uses individual hematocrit values, automatically defines subject‐specific uptake intervals, and fits tracer‐uptake curves by incorporating these measures. The association between reference 99m Tc‐DTPA GFR and MR‐GFRs obtained by SS‐2C, three published 2C uptake, and inflow–outflow models was investigated via linear regression analysis. Uptake intervals varied from 64 sec to 141 sec [96 sec ± 21 sec] and hematocrit values ranged from 30% to 49% [41% ± 4%]; these parameters can therefore not be assumed as constants in 2C modeling. Our MR‐GFR estimates using the SS‐2C model showed accordingly the highest correlation with 99m Tc‐DTPA‐GFRs ( R 2  = 0.76, P  < 0.001) compared with other models (R 2 ‐range: 0.36–0.66). In conclusion, SS‐2C modeling of DCE‐MRI data improved the association between GFR obtained by 99m Tc‐DTPA and Gd‐DTPA DCE‐MRI to such a degree that this approach could turn into a viable, diagnostic GFR assay without radiation exposure to the patient. Abstract : This work focuses on the use of dynamic contrast‐enhanced (DCE) magnetic resonance imaging (MRI) to measure split renal function noninvasively without exposing patients to ionizing radiation. However, application of DCE‐MRI is currently limited because there are (1) only a few cross‐calibration studies with reference glomerular filtration rate (GFR) techniques, and (2) there is a variety of MR tracer models published which causes confusion on the model selection. We report DCE‐MRI‐based GFR measurements using an optimized tracer model (SS‐2C) as well as previously published models in comparison with 99m Tc‐DTPA serum clearance reference GFR measurements in 29 long‐term survivors of Wilms' tumor. Our MR‐GFR estimates using the SS‐2C model showed the highest correlation with 99m Tc‐DTPA‐GFRs ( R 2  = 0.76, P  < 0.001) compared with other models ( R 2 ‐range: 0.36–0.66). Therefore, we believe that our work provides clarification on MR tracer modeling and represents an important step toward integration of MR‐based GFR quantification into diagnostic nephrology.